Peranan Ekonomi Digital Dalam Sistem Pendidikan - Yovi Yanti; Nuraini Asriati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
The economics of education is not only concerned with financial discussions, but also with the aim of improving the quality of education, determining educational policies, and considering education as an important driver of innovation for economic competitiveness. Digital is closely related to technology, which continues to develop to support all human needs. This article aims to determine the role of the digital economy in the education system. The method used is PRISMA, there are 5 stages used, namely determining eligibility criteria, determining information sources, selecting literature, collecting data, and selecting data items. With this method it can be obtained from various sources including journals, books, documentation, the internet and libraries. The research data used is secondary data in the form of accredited journals from the 2014-2024 period. From the 12 articles analyzed, it can be seen the role of the digital economy in the education system, namely as input for digital skills and understanding of technology as an integral part of the curriculum. Can provide skills such as digital literacy, technical problem solving, critical thinking, and online collaboration, and the digital economy also plays a role such as digital education services such as payments, use of e-learning in learning, online libraries.